Committed critical theory: Some thoughts on Stephen White's A Democratic Bearing. (February 2018) - Forst, Rainer
In this article, I comment on Stephen White's version of critical theory as presented in A Democratic Bearing . I specifically focus on his version of the "colonization thesis" and the social analysis this leads to. I also scrutinize his normative framework, especially the claim of non-foundationalism and the difference between his view and Kantian discourse theory.